The regulatory approvals of immune checkpoint inhibitors in China and the United States: A cross‐national comparison study. Issue 11 (18th January 2023) - Jin, Yan; Li, Hongtao; Zhang, Pei; Yu, Man; Zhang, Huan; Li, Xin
Abstract: Immune checkpoint inhibitors (ICIs) are currently one of the most popular treatment methods for cancers. Several ICIs have been approved in China and the United States. We created a database of approved ICIs by extracting the information of interest from the drug labels and reviewing documents disclosed on the official websites of the US Food and Drug Administration (FDA) and the Center for Drug Evaluation (CDE) of the China National Medical Products Administration (NMPA) and compared the difference between the marketed ICIs in China and the United States regarding the number of indications, tumor types, review time, treatment setting, and so forth. Until June 30, 2022, 9 and 15 ICIs had been approved for 86 and 58 indications in the United States and China, involving 20 and 14 types of tumors, respectively. The correlation between indications and disease incidence was higher in China ( r = 0.64) than in the United States ( r = 0.45). About half of the indications were approved as first‐line therapies in combination with chemotherapy, target therapy, or immunotherapy. Over 30% of indications were approved under accelerated or conditional approval in the two countries. A shorter regulatory review time was required by the FDA (median:181 days) compared to the NMPA (median: 279 days) for the new indication approval. Five ICIs marketed in China were approved by the FDA before the NMPA, with the median launch delay for the same indication of 344 days in China. A differentiated clinical development program that focuses on meeting unmet needs may bring new success for subsequent ICI products. Abstract : What's new? Our study comprehensively compares the immune checkpoint inhibitors (ICIs) currently marketed in China and the United States. ICIs have been approved for similar indications in the two countries, especially for metastatic or advanced solid tumors. Programmed cell death protein 1 inhibitors have more indications than programmed death ligand 1 inhibitors. In recent years, ICIs have been moving toward early‐stage disease with an increasing number of indications approved as adjuvant or neoadjuvant therapies. With 15 ICIs already approved in China and 9 in the United States, a differentiated clinical development program focusing on unmet medical needs may bring new success.